The Impacts of the Pertukaran Mahasiswa Merdeka Program on Students’ Academic Performance - Masbirorotni; Abrar, Mukhlas; Fajaryani, Nunung; Failasofah; Nisa, Zahra Syifa"un (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to determine what factors affect the academic side of students during the Pertukaran Mahasiswa Merdeka (PMM) activities. It focused on the positive and negative academic effects experienced by English language education students at Universitas Jambi following the Merdeka Belajar Kampus Merdeka (MBKM) program, especially for batches 1, 2, and 3 of the Pertukaran Mahasiswa Merdeka (PMM) program. The researchers used a qualitative method to reveal the effect of the Pertukaran Mahasiswa Merdeka (PMM) program on English study program students' academic performance. This research was conducted in the English study program at Universitas Jambi with ten participants. The data of this research were collected using interviews and documentation. The interviews contained experiences from the academic side of students based on interview questions. The results of the data analysis found a positive and negative effect on student academic achievement after participating in Pertukaran Mahasiswa Merdeka (PMM) activities and the reason they follow this program.